Serum Insulin-like growth factor-1 levels of healthy adults in southern China - Ji, Wen; Li, Yan-bing; Zhang, Lu-yao; Wan, Jian-xin; He, Wei; Liao, Zhi-hong; Yin, Qi-qi (ENDOCRINE JOURNAL, 2016)
It is to establish the normal range and investigate the distribution characteristics of serum Insulin-like growth factor-1 (IGF-1) for healthy adults in southern China. IGF-1 levels of 515 healthy adults (254 males and 261 females) were measured by automated chemiluminescence immunoassay. The subjects were strictly selected healthy volunteers, aged 20 to 84 years old, with equal five year intervals and without abnormal conditions that impacted IGF-1 levels. The reference ranges were calculated using the smooth centile curves of the LMS method (L: coefficient of skewness, M: median, S: coefficient of variation). IGF-1 declined with aging in adults. There were statistically significant differences for the IGF-1 levels between men and women in some subgroups of age. Gender differences varied depending on the age. Middle-aged females had higher IGF-1 whilst elder females had lower IGF-1. The statistical differences were seen in three subgroups of age between this study and a German cohort that is the reference range for the laboratory test kit. Here, the age- and gender-specific normal range was established for Chinese adults. A Z Score of IGF-1 for an individual could be obtained via the LMSchartmaker application, which standardized IGF-1 research worldwide.